Pedagogika „na twardo” i/lub „na miękko”? - Śliwerski, Bogusław (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The article elaborates on the condition of partial moral anomy in the academic environment, in Poland that not only weakens the ethical causal power of scientific staff, but also results in weakening social capital and also in pathologies in the process of scientific promotion. The narration has been subject to a metaphor of eggs (equivalent of types of scientific publications or a contradiction thereof) and their hatching in various types of hens breeding (scientific or pseudo academic schools) in order to sharpen the conditions and results of academic dishonesty and dysfunction and to notice problems in reviewing scientific degrees and titles’ dissertations.